Determining key health behaviour priorities for subclinical depression using the Fuzzy Delphi method: Perspectives of counseling psychology practitioners - Ibrahim, Taufiq; Ayub, Norzihan; Ading, Carmella E (Journal of Islamic, Social, Economics and Development, 2026)
Subclinical depression, refers to a mild form of depressive disorder that does not meet the full diagnostic criteria for Major Depressive Disorder (MDD). Despite its subthreshold nature, it exerts a significant impact on individuals’ daily functioning, psychological well-being, and overall quality of life, while also increasing the risk of progression to major depression. Although often perceived as “mild,” subclinical depression is associated with health behaviour practices. In Malaysia, mental health concerns have become increasingly prevalent. The NHMS 2019 reported that 500,000 adults (2.3%) suffer from depression, while among adolescents the prevalence of depressive symptoms increased from 17.7% (2014) to 33.1% (2019). Importantly, many of these cases fall under subclinical categories not meeting full diagnostic thresholds but still impairing functioning. This study aims to identify and prioritize the primary health behavior constructs for individuals with subclinical depression, based on the consensus of counseling psychology practitioners using the Fuzzy Delphi method. This study shows that health behaviours in subclinical depression follow a clear expert-defined hierarchy. Sleep behaviour is the primary and foundational factor, supported by social relationships and daily routine with behavioural activation as key recovery mechanisms. Psychological resilience and coping capacity play a sustaining role, while physical activity and diet act as secondary supports. Life stressors are mainly contextual, highlighting the need to prioritise core self-regulation and behavioural activation in interventions.